Diagnostic Performance of Des-γ-carboxy Prothrombin for Hepatocellular Carcinoma: A Meta-Analysis - Rong Zhu; Jing Yang; Ling Xu; Weiqi Dai; Fan Wang; Miao Shen; Yan Zhang; Huawei Zhang; Kan Chen; Ping Cheng; Chengfen Wang; Yuanyuan Zheng; et al. (Gastroenterology Research and Practice)
Background. There have been many reports on des-γ-carboxy prothrombin (DCP) as a promising serum marker in the diagnosis of hepatocellular carcinoma (HCC); however, the results are inconsistent and even conflicting. Methods. This meta-analysis was performed to investigate the performance of DCP in the diagnosis of HCC. Following a systematic review of relevant studies, Meta-DiSc 1.4 software was used to extract data and to calculate the overall sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). Data are presented as forest plots and summary receiver operating characteristic curve (SROC) analysis was used to summarize the overall test performance. Results. Twelve studies were included in our meta-analysis. The overall sensitivity, specificity, PLR, and NLR of DCP for the detection of HCC in the studies included were 71% (95%CI: 68%–73%), 84% (95%CI: 83%–86%), 6.48 (95%CI: 4.22–9.93), and 0.33 (95%CI: 0.25–0.43), respectively. The area under the SROC curve was 0.8930 and the Q index was 0.8238. Significant heterogeneity was found. Conclusion. This meta-analysis indicated that DCP had moderate diagnostic accuracy in HCC. Further studies with rigorous design, large sample size, and mmultiregional cooperation are needed in the future.